Peran Pesantren dalam Melawan Penjajah Barat di Indonesia - Amin, Ahmad Yasir Al; Anshory, Muhammad Isa (ANWARUL, 2024)
The independence of Indonesia was achieved through a challenging process that involved various elements of the Indonesian people, including the santri community. The role of santri (Islamic students) in Indonesia's independence was evident long before the proclamation of independence on August 17 1945. This article delves deeper into the history and roles of the santri in resisting Western colonizers to fight for Indonesia's freedom. The research methodology employed in this study is a literature review, drawing from various references. We critically and thoroughly analyze these sources to support the ideas and themes we present, specifically focusing on the role of pesantren (Islamic boarding schools) that have consistently resisted colonizers over centuries, inspiring the masses, especially the Muslim community, to enrich the Islamic historiography: the role of ulama-santri (Islamic scholars and students) in realizing a prosperous nation under the guidance of Allah within the framework of the Republic of Indonesia. The heroic stories of the pesantren community are not only passed down orally from generation to generation but are also recorded in Indonesia's historical records.